Assessment and Prevalence of Communicable and Non-Communicable Diseases and their Risk Factors in Adults - Arif, Urooj; Thanveer, Shaik Aamena; Rakshitha, P; Gowtham, N; Sameera, Amatul Ali; Amrohi, Nazia Lateef (Journal of Neonatal Surgery, 2025)
Aim and objectives: To perform a prospective study on assessment of occurrence of communicable and non-communicable diseases and study their risk factors in adults. Methodology: The study was conducted at Aware Gleneagles global hospitals in L.B. Nagar, Hyderabad, over a 6 months period among 115 subjects in the study. Patients of both genders age between 18 to 55 years and comorbidities were included in the study. Patients with OP patients, pregnant patients, patients on other medication systems (ayurvedic, Unani and homeopathy), neonates were excluded from the study. Any patient with comorbidities who are at risk of developing communicable or non-communicable diseases had their information collected using a data collection form that included patient’s demographics, prescription charts, laboratory investigations, medical history and other required information. Result: A study of 115 patient records revealed a demographic split of 60 males (52.2%) and 55 females (47.8%). The data showed 50 cases (43.5%) of communicable diseases and 65 cases (56.5%) of non-communicable diseases. Notably, 65 patients had comorbid conditions, primarily hypertension and diabetes. The 51-55 age group was disproportionately affected by both communicable and non-communicable diseases. Pseudomonas aeruginosa was identified as the most common microorganism causing Lower Respiratory Tract Infections (LRTI). The most prevalent communicable diseases were viral pyrexia and LRTI, while Urinary Tract Infections (UTI) and acute gastroenteritis were the most common non-communicable diseases. Overall, the study found a higher incidence of communicable diseases compared to non-communicable diseases. Conclusion: This study examined 115 subjects affected by diverse communicable and non-communicable diseases, revealing varying prevalence rates among the participants over the study period.